2015
DOI: 10.1016/j.cma.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Computational cost of isogeometric multi-frontal solvers on parallel distributed memory machines

Abstract: This paper derives theoretical estimates of the computational cost for isogeometric multi-frontal direct solver executed on parallel distributed memory machines. We show theoretically that for the C p−1 global continuity of the isogeometric solution, both the computational cost and the communication cost of a direct solver is of order O(log(N )p 2 ) for the one dimensional (1D) case, O(N p 2 ) for the two dimensional (2D) case, and O(N 4/3 p 2 ) for the three dimensional (3D) case, where N is the number of deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Moreover we plane to execute the whole system on a parallel distributed memory Linux cluster, using efficient isogeometric multifrontal direct solvers [14,11], as well as porting this algorithm to a GPU environment, using our fast GPU solver for linear algebraic systems [13].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover we plane to execute the whole system on a parallel distributed memory Linux cluster, using efficient isogeometric multifrontal direct solvers [14,11], as well as porting this algorithm to a GPU environment, using our fast GPU solver for linear algebraic systems [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the final part of the paper we conclude with performance measures of a shared-memory implementation of the algorithm (see also [10,12]) and useful remarks for the potential implementations of the solvers.…”
Section: Background and Motivationmentioning
confidence: 99%
“…We analyzed the parallel scalability of highly-continuous IGA systems in [35], where we showed that the direct solution of IGA systems has similar parallel scalability properties to standard C 0 FE systems. Although the performance of the direct solution of IGA systems is significantly worse than that of FE systems for a fixed number of degrees of freedom.…”
Section: Solution and Communication Cost Estimatesmentioning
confidence: 99%